THE ROLE OF PREVENTIVE OBSTETRICS IN REDUCING PERINATAL MORTALITY - Hromova, A.M.; Hromova, O.L.; Mitiunina, N.I.; Martynenko, V.B.; Shafarchuk, V.M.; Orlova, Y.A. (World of Medicine and Biology, 2024)
Implementing the latest technologies and programs aimed at helping the mother and the newborn contributed to the development of both perinatal and preventive obstetrics. The role of preventive obstetrics is aimed at predicting and preventing, if necessary, perinatal consequences. The World Health Organization has developed guidelines for effective perinatal care: evidence-based, demedicalized, technology-based, multidisciplinary, family-centered, and regionalized. In Ukraine, as in the world, among the causes of perinatal mortality, the death of premature children with meagre body weight (up to 70 %) and congenital malformations and anomalies (22–24 %) prevails. Perinatal obstetrics involves the development of a network of perinatal centres and hospitals according to the degree of development, as well as the reorganization and development of neonatal services. There should be provision of intensive therapy, the possibility of raising premature babies, and the availability of highly qualified specialists. Thus, the preventive direction of perinatal obstetrics should be based on deep knowledge of the basics of classical obstetrics during the physiological course of pregnancy and childbirth; limited (prohibitions), aggressive obstetrics with hyperpolarization of obstetric activity, which, as a rule, is based on a misunderstanding (ignorance) of perinatal obstetrics. “Management” of pregnancy and childbirth in case of risk (presence) of diagnosed fetal morbidity, manifestations of intrauterine infection, autoimmune pathology, and pathology of the placental complex in the presence of modern technologies that ensure the development of the newborn.
Keywords: perinatology; development of obstetric hospitals; perinatal centers; regionalization; caesarean section